Total phenolic and total flavonoid contents, free radical scavenging activity and tyrosinase inhibitory potential from the methanolic extracts of Cajanus cajan (L.) Millsp. and Acacia concinna (Willd.) DC. Flowers. - มณีฉาย สุธิรา; รินทอง ประสบอร (KKU Science Journal, 2016)
The present research was aimed to determine total phenolic and total flavonoid contents, antioxidant activity, tyrosinase inhibitory capacity of Cajanus cajan (Fabaceae) and Acacia concinna (Fabaceae) flowers. The methanolic crude extracts of C. cajan (CC) and A. concinna (AC) were prepared by reflux method. The results showed that total phenolic contents of CC and AC were 113.54±2.75 and 60.96±3.64 mg of gallic acid equivalent /g extract, respectively. The flavonoid contents were 0.22±0.03 and 0.98±0.01 mg of quercetin equivalent /g extract, respectively. Both extracts were also investigated their antioxidant activities using DPPH and ABTS assays. Based on DPPH method, IC50 of CC and AC were 0.66±0.03 and 0.94±0.02 mg/mL. For ABTS assay, IC50 of CC and AC were 0.60±0.02 and 0.84±0.01 mg/mL, respectively. The tyrosinase inhibitory activities of CC and AC were also determined. Their IC50 values were 2.21±0.16 and 1.91±0.09 mg/mL, respectively.